DETERMINANT OF MARITAL QUALITY IN NEWLY MARRIED COUPLE DURING THE COVID-19 PANDEMIC - Ira Mustika; Tin Herawati (Journal of Child, Family, and Consumer Studies, 2022)
New challenges regarding marriage readiness and adjustment emerged during the Covid-19 pandemic for newly married couples. Marriage readiness and adjustment are essential in realizing a good marriage quality. This study analyzes the relationship and influence of family characteristics, marriage readiness, and marriage adjustment on marriage quality in newly married families during the Covid-19 pandemic. The design of this study used a cross-sectional study. This study involved 39 wives with criteria for marriage age less than two years and who have not had children. Data were collected through direct interviews using questionnaires, and the research location was conducted in Dramaga Village, Bogor Regency. The results of the descriptive analysis show that most newly married couples have marriage readiness in the ready category and have marriage adjustment and quality in the high class. The results of the inferential analysis show that per capita income is significantly positively related to marital adjustment. Marriage readiness and marriage adjustment are significantly positively related to marital quality. A wife's education and marriage length significantly adversely affect marriage quality. Per capita income and marriage adjustment significantly positively affect marital quality. Based on the study's results, newly married couples need to make suitable marriage adjustments to achieve good marriage quality. This research implies that the government is expected to optimally implement the marriage guidance program before marriage and provide programs that can improve the ability to adjust to marriage, such as family life counseling.